Hydrographic data modeling methods for determining precise seafloor topography - Aykut, Nedim Onur; Akpinar, Burak; Aydin, Omer (SPRINGER, 2013)
Acoustic and light detection and ranging are the recent methods used in hydrographical surveying. Depth values depending on X and Y horizontal coordinates are measured in both methods. While processing the hydrographical data, all data with different density are interpolated and modeled for determining the seafloor model using different interpolation techniques. In this study, effects of different surface modeling methods are investigated. Data obtained from single-beam echo sounder (SBES) are modeled using inverse distance, kriging, local polynomial, minimum curvature, moving average, nearest-neighbor, and Delaunay interpolation methods. Interpolation results are compared with the multibeam echo sounder data which were collected on the same area for determining the accuracy of modeling methods. Depending on the maximum total vertical uncertainty values in hydrographic survey standards, the best results were determined by using the kriging method. The Delaunay, minimum curvature, and inverse distance methods can be used for modeling the SBES data in shallow waters.
Keywords: Seafloor topography; Bathymetric modeling; Acoustic depth measurement; Digital elevation model; Computer Science; Geology